Intensification as a Multilevel System of Modern English (Texas Journal of Philology, Culture and History, 2022)
The article under discussion depicts intensification as a multilevel system of modern English. The intensification of an utterance is realized at phonetic (graphic representation), morphological, lexical, syntactic and textual linguistic levels. The author of the article considers that the problems of the use of intensifiers, their functioning, and combinability may also be of interest for further research in this field